Environmental perceptions and health before and after relocation to a green building. (1st August 2016) - MacNaughton, Piers; Spengler, John; Vallarino, Jose; Santanam, Suresh; Satish, Usha; Allen, Joseph
Abstract: Green buildings are designed to have low environmental impacts and improved occupant health and well-being. Improvements to the built environment including ventilation, lighting, and materials have resulted in improved indoor environmental quality (IEQ) in green buildings, but the evidence around occupant health is currently centered around environmental perceptions and self-reported health. To investigate the objective impact of green buildings on health, we tracked IEQ, self-reported health, and heart rate in 30 participants from green and conventional buildings for two weeks. 24 participants were then selected to be relocated to the Syracuse Center of Excellence, a LEED platinum building, for six workdays. While they were there, ventilation, CO2, and volatile organic compound (VOC) levels were changed on different days to match the IEQ of conventional, green, and green+ (green with increased ventilation) buildings. Participants reported improved air quality, odors, thermal comfort, ergonomics, noise and lighting and fewer health symptoms in green buildings prior to relocation. After relocation, participants consistently reported fewer symptoms during the green building conditions compared to the conventional one, yet symptom counts were more closely associated with environmental perceptions than with measured IEQ. On average, participants had 4.7 times the odds of reporting a lack of air movement, 43% more symptoms (p-value = 0.019) and a 2 bpm higher heart rate (p-value < 0.001) for a 1000 ppm increase in indoor CO2 concentration. These findings suggest that occupant health in green and conventional buildings is driven by both environmental perceptions and physiological pathways. Graphical abstract: Highlights: Participants in green buildings experience better indoor air quality and improved environmental perceptions. Participants in green buildings report fewer symptoms than those in conventional buildings. Participants report fewer symptoms in simulated green buildings conditions in controlled lab. A 1000 ppm increase in CO2 is associated with a 1.43 increase in symptoms and a 2.3 bpm increase in heart rate.